UJI BERBAGAI HERBISIDA DALAM MENGENDALIKAN GULMA PADA PERTANAMAN PADI SAWAH TEBAR LANGSUNG DAN KEDELAI DI LAHAN BASAH - Risvan Anwar (Jurnal Agroqua, 2017)
The purpose of the research was to know effect some kind herbicides to control the weeds paddy direct seeded and soybean in wet areal. A randomized block design was used 3 replications and 8 treatments namely: (A) Agristar; (B) Ally Plus; (C) DMA; (D) Metafuron; (E) Agristar and DMA 6; (F) Agristar and Metafuron; (G) Ally Plus and DMA 6; (H) Ally Plus and Metafuron. The result suggested that just pre plant herbicides (Ally Plus and Agristar) or post emergence herbicides (DMA 6 and Metafuron) only was not effective to control the weeds paddy direct seeded and soybean in wet areal. Pre plant herbicide (Ally Plus) that next is followed post emergence DMA 6 most effective to control the weed paddy direct seeded and soybean in wet areal.